Similarities and Differences in Alcohol & Other Drug Dependence Among Hispanic/Latino Subgroups: A Disaggregation Approach - Virmarie Correa-Fernández; Adnan M. Barazi; Madhur Chandra; James C. Anthony (Drug and Alcohol Dependence Reports, 2022)
Background: Hispanic/Latino (H/L) heritage civilians out-number all other non-White ethnic groups in the United States. When studied as one group, H/L diversity is ignored, including rates of drug misuse. This study's aim was to examine H/L diversity regarding drug dependence by disaggregating how the burdens of active alcohol or other drug dependence (AODD) might change if we were to address syndromes drug by drug. Method: Studying non-institutionalized H/L residents from the National Surveys on Drug Use and Health (NSDUH) 2002-2013 probability samples, we utilized online Restricted-use Data Analysis System variables to identify ethnic heritage subgroups and active AODD via computerized self-interviews. We estimated case counts of AODD with analysis-weighted cross-tabulations and variances from Taylor series. Radar plots disclose AODD variations when we simulate the reductions of drug-specific AODD one by one. Results: For all H/L heritage subgroups, the most substantial AODD decline might be achieved by reducing active alcohol dependence syndromes, followed by declines of cannabis dependence. The burdens due to active syndromes attributed to cocaine and pain relievers vary somewhat across subgroups. For the Puerto Rican subgroup, our estimates reveal potentially important burden reduction if active heroin dependence can be decreased. Conclusion: A sizeable reduction in the H/L population health burden attributable to AODD syndromes might be achieved via the effective decline of alcohol and cannabis dependence among all subgroups. Future research includes a systematic replication with recent NSDUH survey data, as well as various stratifications. If replicated, the need for targeted drug-specific interventions among H/L will become unequivocal.